On the Technical Characteristics of Insurance Operations and Financial Performance of Non-life Insurance Companies in Nigeria.: Array - Abass, Olufemi; Dansu, Sewhenu Francis; Oyetayo, Yeside Abiodun (The Journal of Accounting and Management, 2021)
The inverse cycle nature of insurance business suggests the adoption of unique firm characteristics upon which its operations rely. These characteristics to a large extent determine risk exposure, underwriting capacity, risk appetite, risk tolerance among others. This study evaluated the impact of these technical characteristics on the financial performance on non-life insurance companies in Nigeria. This study adopted descriptive research design and relied on secondary data of all the non-life companies operating in Nigeria between 2006-2019. Data were gathered from the annual financial statements as contained in NIA, a publication of Nigeria Insurers Association. The study used firm size, premium growth, loss ratio, liquidity, investment, capital adequacy, reserves and underwriting capacity as proxies of technical characteristics while return asset, return on equity and return on investment were used as proxies of financial performance. The results revealed a significant impact of joint technical characteristics variables on the financial performance. Specifically, the study revealed that reserves, shareholders’ fund, firm size, capital adequacy and premium growth are the main technical characteristics that influence the financial performance. The study recommended that non-life insurance companies must constantly monitor their reserves, increase shareholders fund, increase capital base, capital adequacy, and grow their portfolio through premium generation.